KESESUAIAN LAHAN EKOWISATA GURUN PASIR DESA BUSUNG KABUPATEN BINTAN - Tyas Rosani; Primantoro Nur Vitrianto2 (Media Bina Ilmiah, 2023)
Busung Village is located in Bintan Regency, Riau Island Province has a viral attraction, there is a Desert and Blue Lake. This destination managed by local community become an interesting natural attraction. Based on the Bintan Government Regulation Number 1 year 2020 about Regency Spatial Planning Policy, Busung Village is the part of Industrial Area. Meaning that the Desert and Blue lake is located inside the industrial area. To develop a tourism destination is not only to develop the Attraction, Accessibility, Amenity and Ancillary Service only, however it needed a site suitability evaluation. The aim of this research is to evaluate of site suitability of Busung Village based on ecotourism criteria. The other purpose is to provide the development guidance for Busung village for the future. This research is using mixed method, the quantitative is used to evaluate the site suitability for ecotourism. To explain the ecotourism suitability index is using the descriptive method. Data was analyzed by spatial analysis and software Geographic Information System (GIS). The result showed that the ecotourism suitability index for sample I is 71,34% and sample II is 70,12%. All sample in the S2 category which mean that area are suitable for ecotourism. Based on the spatial map, the development guidance for the Desert and Blue Lake area is 18,49 hectares for ecotourism activity.